Litteratur og subjektivitet - Johansen, Jørgen Dines (K&K - Kultur og Klasse, 2006)
Literature and subjectivity Literature, it is claimed, is the discourse that is able to represent man’s experience of existence in its totality, but simultaneously as fragmented. The human species is characterized by unique brain capacity, long childhood, no mating seasons, longevity, and the possibility of entering into complex social and labour relations. In addition, man is always, by necessity, bound to his own mind and body, to the privileged other, to others, and to outer nature. And these relationships are what makes literature possible. With Piaget, it is argued that literature is built on the semiotic function developed in early childhood, i.e., the ability to represent, and to change the surrounding world in memory and in fantasy. Hence, fictionality, an important feature of literature, is something that characterizes our mental activity in general, and it serves to liberate us from reality;simultaneously it helps us to interpret it.